Evaluation of the serum biochemistry and haematology of rabbits fed straws and haulms diets - Awang, Z. E.; Shaahu, T.D.; Tuleun, D.C.; Okpanachi, U.; Okwori, I.A. (Nigerian Journal of Animal Science, 2023)
With the current unavailability and competition for crop products in the country, there is a need to conserve crop residues, which are found here in Jos, Plateau State, and supplement them in feeding animals, especially during the dry season when fresh forages are not readily available or obtainable. The serum biochemistry and haematology of exotic breeds of rabbits were evaluated. Forty-two (42) weaner rabbits with an average weight of 922.08 g were utilized for the investigation. The haematological and serum biochemical indices were monitored after twelve (12) weeks of feeding. Six (6) rabbits with three (3) males and three (3) females were grouped into seven (7) treatments with individual rabbits as a replicate in a completely randomized design (CRD). Control groups were fed with feeds containing rice offal; while the six (6) groups from diet 2 (D2) to diet 6 (D3) in which D2 contained 20% acha straw; D3 contained 20% rice straw; D4 contained groundnut haulms; D5 contained cowpea haulms, D6 contained 20% (50% groundnut and 50% groundnut haulms) D7 contained 20% of (50% rice straw and 50% cowpea haulms). After the feeding trial, the blood samples were collected from the ear veins for serum biochemical and Hematology study. The result showed that alanine aminotransferase (ALT), aspartate transaminase (AST), total bilirubin, and glucose were significantly different between the treatments; while the total albumin, total protein, urea and creatinine had no significant difference. For haematology there were no significant differences between treatments for PCV, HB, RBC, L, M, E, B, PEP, and POS except for RBC and WBC which had a significant difference of 5% between the treatments. This study indicated that the use of 20 % straw and haulms in diets alongside other feedstuff will meet the nutritional needs of rabbits and aid adequate healthy blood formation and circulation at a similar level to the control diet. It is therefore recommended for rabbit farmers and feed manufacturers.